GOLD IN TURKEY - A MISSING LINK IN TETHYAN METALLOGENY - Yigit O. (My University, 2006)
The gold metallogeny of Turkey constitutes a sector of the Tethyan Eurasian Metallogenic Belt (TEMB) within the Alpine-Himalayan orogenic system that formed from Jurassic-Cretaceous to the present. This orogenic system produced many different types of deposits related to subduction, collision, post-collision and rifting processes. Gold deposits, as well as other mineral deposits of Turkey, are mainly concentrated in Late Mesozoic and Tertiary rocks. Evaluation of the gold metallogeny of Turkey is based on a GIS database compilation of known gold deposits and prospects. Currently available data show that Turkey has a gold endowment, including reserves and resources, of approximately 31.5 M oz [979 tonnes] in 51 deposits, 21 of which contain more than 0.2 M oz gold. The other 30 deposits contain a total of approximately 1 M oz [31 tonnes] gold resources. Two recent discoveries, Kisladag and Copler, currently contain total resources of 17.6 M oz Au [549 tonnes], more than 50% of the total Turkish gold endowment. Turkey possesses a wide spectrum of gold deposits related to Mesozoic and Cenozoic volcanoplutonic arcs. However, porphyry gold (copper), epithermal gold (including both high- and low-sulfidation styles), and gold-rich volcanic-associated massive sulfide (including both Kuroko- and Cyprus-types) are the most economically important to date. Orogenic gold, including listwanite-hosted, placer gold and skarn-hosted gold are relatively less important or abundant deposit types. Other potential gold systems for exploration include Carlin-type gold, detachment-fault-related gold, iron oxide-copper-gold, and gold in carbonate-replacement and manganese deposits. © 2005 Elsevier B.V. All rights reserved.
Keywords: GOLD; ISLAND ARC; MAGMATIC ARC; MINERAL EXPLORATION; PONTIDES; TETHYAN METALLOGENY; TETHYS; TURKEY; Cretaceous; Jurassic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская